2018
DOI: 10.3390/antiox7090117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Cooking Methods on Polyphenols, Carotenoids and Antioxidant Activities of Selected Edible Leaves

Abstract: This study aimed to evaluate the effect of cooking (boiling, steaming, and frying) on polyphenols, flavonoids, carotenoids and antioxidant activity of six edible leaves. The total antioxidant capacity of the fresh and cooked leaves was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and singlet oxygen scavenging assays. The results revealed that frying caused a reduction in major bioactives and antioxidant activities in all leafy vegetables tested. However, steamed and boiled leaves of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 37 publications
10
70
0
1
Order By: Relevance
“…The amount of tannins in Moringa oleifera leafy vegetables increased by 13.79% and 30.67% as a result of wet frying and boiling the vegetables for ten minutes respectively. These results agrees with Gunathilake et al,2018 where it was found that in some vegetables, tannins content increase due to breakdown of the complex tannins compounds present in the vegetables during heat processing to simple tannins. Also, increase in total polyphenols such as tannins during thermal processing might be due to the liberation of polyphenols from the intracellular protein complexes, changes in plant cell structure, matrix modifications, or the inactivation of the polyphenol oxidases (Gunathilake et al, 2018).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The amount of tannins in Moringa oleifera leafy vegetables increased by 13.79% and 30.67% as a result of wet frying and boiling the vegetables for ten minutes respectively. These results agrees with Gunathilake et al,2018 where it was found that in some vegetables, tannins content increase due to breakdown of the complex tannins compounds present in the vegetables during heat processing to simple tannins. Also, increase in total polyphenols such as tannins during thermal processing might be due to the liberation of polyphenols from the intracellular protein complexes, changes in plant cell structure, matrix modifications, or the inactivation of the polyphenol oxidases (Gunathilake et al, 2018).…”
supporting
confidence: 92%
“…Significant losses of tannins were reported by Jugran, A. K., & Chaudhary, W. Y.,2016 in Peeonia emodi leaves after boiling the leaves from different stages of growth. The losses of tannins due to boiling and frying are attributed to thermal degradation of tannins during cooking as reported by Gunathilake et al, 2018. In this study, the amount of tannins in wet fried jute mallow increased by 8.09% compared to the dry uncooked jute mallow.…”
supporting
confidence: 67%
“…Since, polyphenols are used as food additives, it is also interesting to find out how cooking affects their antioxidant activity. Gunathilake et al [38] examined the effect of cooking (boiling, steaming, and frying) on the antioxidant activity of polyphenols from edible leaves of six species, Centella asiatica, Cassia auriculata, Gymnema lactiferum, Olax zeylanica, Sesbania granadiflora, and Passiflora edulis. The findings demonstrated that frying decreased polyphenols, flavonoids, carotenoids, and their antioxidant activities in all leafy vegetables [38].…”
mentioning
confidence: 99%
“…Gunathilake et al [38] examined the effect of cooking (boiling, steaming, and frying) on the antioxidant activity of polyphenols from edible leaves of six species, Centella asiatica, Cassia auriculata, Gymnema lactiferum, Olax zeylanica, Sesbania granadiflora, and Passiflora edulis. The findings demonstrated that frying decreased polyphenols, flavonoids, carotenoids, and their antioxidant activities in all leafy vegetables [38]. The effects of boiling and steaming on polyphenols, carotenoids, and their antioxidant properties, varied according to the leaf type [38].…”
mentioning
confidence: 99%
“…The main antioxidant component of papaya waste itself is polyphenol (Verghese et al, 2016). Polyphenol has a high sensitivity level so it is possible that it was damaged during process (Gunathilake et al, 2018).…”
Section: Antioxidant Activity Of ß-Glucan From S Cereviseae With Vegmentioning
confidence: 99%